2021
DOI: 10.3390/ijms22147596
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Transcriptome and Metabolome Reveals the Genes and Metabolites Involved in Bifidobacterium bifidum Biofilm Formation

Abstract: Bifidobacterium bifidum strains, an important component of probiotic foods, can form biofilms on abiotic surfaces, leading to increased self-resistance. However, little is known about the molecular mechanism of B. bifidum biofilm formation. A time series transcriptome sequencing and untargeted metabolomics analysis of both B. bifidum biofilm and planktonic cells was performed to identify key genes and metabolites involved in biofilm formation. Two hundred thirty-five nonredundant differentially expressed genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Integrative analysis of transcriptomic, proteomic, and metabolomic data has been widely used to study biofilms in recent years [ 40 42 ]. Preliminary experiments found that the biofilms treated with CRAMP at a concentration of 62.5 µg/mL for 1 h exhibited the best eradication effect, and the changes in the transcription levels of biofilm-related genes were evident under this experimental condition.…”
Section: Discussionmentioning
confidence: 99%
“…Integrative analysis of transcriptomic, proteomic, and metabolomic data has been widely used to study biofilms in recent years [ 40 42 ]. Preliminary experiments found that the biofilms treated with CRAMP at a concentration of 62.5 µg/mL for 1 h exhibited the best eradication effect, and the changes in the transcription levels of biofilm-related genes were evident under this experimental condition.…”
Section: Discussionmentioning
confidence: 99%
“…YidC function as integral membrane chaperone/insertase associated with the classical SecYEG translocon, which could contribute to inhibit biofilm formation ( Hofbauer et al., 2018 ). The upregulated expression of the secY and yidC genes involved in extracellular polymeric substances was also observed in the stage of biofilm maturation of Bifidobacterium Longun FGSZY16M3 ( Liu et al., 2021 ). In this study, the secF gene expression was also highly increased by 2.06 fold, which encodes a component of the Sec translocon.…”
Section: Resultsmentioning
confidence: 94%
“…79 The ABC transporter protein was reported by Liu et al to be crucial in the formation of B. longum when studying the gene level differences between bacterial cells in biofilms and suspensions. 80 Using the two-component system was the primary strategy for microorganisms to respond to environmental changes and control their gene expression. For example, QseC found in Haemophilus parasuis , which was related to the two-component system, was mainly involved in stress tolerance and biofilm formation.…”
Section: Discussionmentioning
confidence: 99%